Real-World Experience With Antiplatelet Agents After Percutaneous Coronary Intervention in Patients With an Indication for an Oral Anticoagulant. Issue 4 (April 2021) - Tanner, Richard; Cronin, Michael; Macken, Lilly; Murphy, Ross; Maree, Andrew O.; Ullah, Ihsan; Cosgrave, John; O'Connor, Stephen; Daly, Caroline
Abstract : Abstract: Patients undergoing percutaneous coronary intervention (PCI) with a clinical indication for oral anticoagulation (OAC) in addition to antiplatelet therapy (APT) necessitate rigorous evaluation of bleeding and ischemic risk to guide therapy. The optimal OAC/APT drug combination and duration of treatment is not known. This study aimed to evaluate the incidence of patients undergoing PCI with an OAC indication and the rationale for post-PCI combined OAC/APT selection in clinical practice. Consecutive patients undergoing PCI with an indication for combined OAC/APT were included in a 12-month retrospective case series. Patient demographics, clinical characteristics, prescribed OAC/APT regimens, and rationale for drug selection were reviewed. PCI was performed in 1650 patients during the study period, with an indication for OAC/APT in 133 (8.1%). A combination of aspirin, P2Y12 inhibitor, and OAC was the most frequently prescribed regime on discharge (n = 103, 81%). Dual antiplatelet therapy (DAPT) in combination with OAC was continued for a mean duration of 6.4 ± 4.4 weeks (range 3–52 weeks) before one antiplatelet was discontinued. There was no significant difference between the mean CHA2 DS2 -VASc or HAS-BLED score of patients with atrial fibrillation discharged on OAC/DAPT compared with alternate combinations (DAPT alone or OAC/single APT), 3.6 ± 1.3 versus 3.8 ± 1, P = 0.37 and 2.04 ± 0.7 versus 2.05 ± 1.0, P = 0.98, respectively. This case series identifies high variability in OAC/APT treatment duration and limited application of risk scoring systems and high-risk PCI characteristics in the selection of OAC/APT regimens. A more systematic patient assessment is needed to help standardize OAC/APT prescribing for this important patient cohort.